Postoperative venous thromboembolism in Asia: A critical appraisal of its incidence - Liew, Ngoh Chin; Moissinac, Kevin; Gul, Yunus (Springer-Verlag Hong Kong, 2003)
OBJECTIVES: Venous thromboembolism (VTE) has historically been perceived to be a rare disorder in Asia. However, new evidence has emerged recently that contradicts this perception. The question of routine VTE prophylaxis has been hotly debated in Asia due to disagreement on its incidence. We reviewed and analysed studies on postoperative VTE in Asian patients to determine if the condition was indeed rare and if the routine prophylactic measures as recommended by internationally accepted guidelines should be adopted in Asia. METHODS: A review of published reports, from 1966 to December 2002, on deep vein thrombosis (DVT) and pulmonary embolism (PE) in the Asian population was made. A literature search of studies published in English was conducted via a detailed MEDLINE search. Studies had to attain a minimum inclusion and quality criteria to be accepted for the review, including the diagnostic modality used for the diagnosis of VTE. The appraisal was carried out independently and accepted by at least two of the three authors. The study population was classified into orthopaedic and general surgical/colorectal groups. RESULTS: Twelve orthopaedic publications reviewed revealed an incidence of postoperative DVT of 10% to 63%. Six general and colorectal surgical publications reported an incidence of DVT ranging from 3% to 28%. The incidence was slightly lower than the reported incidence of 40% to 80% following orthopaedic surgery and 28% to 44% following general surgical operations in studies reporting on Caucasian populations. CONCLUSION: While there is a wide variation in the incidence of DVT and VTE as reported in the Asian population, these diseases are by no means rare. The wide variation could be due to the study designs, heterogeneity of the procedures performed and the application of different diagnostic criteria. Results based on prospective studies with objective diagnostic criteria confirm the incidence of VTE as common. Routine chemoprophylaxis must be seriously considered in high-risk patients.